Cloning, characterization and tissue-specific expression of the antimicrobial peptide hepcidin from caspian trout (Salmo caspius) and the antibacterial activity of the synthetic peptide - Shirdel, Iman; Kalbassi, Mohammad Reza; Hosseinkhani, Saman; Paknejad, Hamed; Wink, Michael (Fish & shellfish immunology, 2019)
Antimicrobial peptides have a wide range of antimicrobial activity and widely occur in different organisms including mollusks, crustaceans and vertebrates. Hepcidins are a group of cysteine-rich antimicrobial peptides that are active against a variety of pathogens including gram-positive and gram-negative bacteria, as well as viruses. In this study, the hepcidin gene of Caspian trout (CtHep) was identified and characterized. Our results showed that CtHep cDNA has a 267-bp Open Reading Frame (ORF), which is translated to 88 amino acids. The CtHep was classified in the HAMP1 class of hepcidins. Comparison of DNA and cDNA sequences showed that CtHep has 3 exons and 2 introns. The signal, prodomain and mature part of CtHep have 24, 39 and 25 amino acids, respectively. The mature peptide has a molecular weight of 2881.43Da and a theoretical isoelectric point of 8.53. The expression of CtHep mRNA was detected in different tissues of healthy and infected fish. CtHep expression in the liver, head kidney, spleen and skin was significantly enhanced after bacterial challenge. Expression of CtHep in different embryonic development stages was also substantial. Antibacterial activity of synthetic CtHep peptides was investigated against a number of Gram-positive and Gram-negative bacteria. CtHep inhibited some pathogenic bacteria such as Streptococcus iniae and Aeromonas hydrophila. In the in vivo experiment, CtHep upregulated the cytokines IL-6 and TNF-α in both kidney and spleen tissues after 24h of the peptide injection. In conclusion, our study showed that CtHep plays an important role in the immune system of Caspian trout and also in the embryonic stages. Moreover, CtHep peptide has a potential to be used as an antimicrobial therapeutic agent as well as an immunostimulant in aquaculture.